Feeding the Future: Text Typology in Agri-Food Translation (2021)
The agri-food sector encompasses an extremely wide range of activities regarding the entire value chain of a product and generates a huge volume of work for translators. Nevertheless, the sheer proportion has yet to be truly reflected in academic studies and research. This work intends to shed light on the vague, and barely addressed until now, delimitation of the area of activity of the multifaceted and versatile agri-food translator. Through a text typologisation of genres and subgenres, within the margins of hybridity, specialisation and register, this work approaches the characteristics of scientific-technical, medical-health, legal-administrative, humanistic-literary, tourist, advertising and gastronomic and culinary agri-food texts, and assesses the skills required from their translator.El sector agroalimentario abarca un amplísimo abanico de actividades que engloban toda la cadena de valor de sus productos, lo que genera un enorme volumen de traducciones; sin embargo, las investigaciones y los estudios académicos apenas se han ocupado de esta especialidad hasta ahora. Este trabajo pretende arrojar luz sobre la poca delimitación del ámbito de actividad del polifacético y versátil traductor agroalimentario y, a través de una tipología textual de géneros y subgéneros, dentro de los márgenes de la hibridez, la especialización y el registro, aproximar a las características de los textos científico-técnicos, médico-sanitarios, jurídico-administrativos, humanístico-literarios, turísticos, publicitarios y gastronómicos y culinarios agroalimentarios, así como evaluar las competencias que exige su traducción.
Keywords: Sector agroalimentario; Traductor agroalimentario; Traducción de textos gastronómicos